2015
DOI: 10.5539/elt.v8n2p70
|View full text |Cite
|
Sign up to set email alerts
|

Can Code Switching Enhance Learners’ Academic Achievement?

Abstract: There has been a high failure rate of Grade 10 learnersin the year end examinations in the Caprivi Education Region of Namibia over a number of years. The objective of this study was to investigate whether the use of mother tongue in English medium classrooms enhanced learners' academic achievement.The study investigated 12 teachers at 12 schools in the Caprivi Education Region. The study found that teachers perceived Code Switching as enhancing academic achievement because it enhanced learners' learning of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…For effective and efficient English language teaching and learning, for instance, [29] advises teachers to use code-switching not only as a means to point out main learning themes and other key tasks but also to point out students' errors and to give immediate correction. This practice does not only enhance students' learning of the English language, as [30] discover, but it also does improve students' engagement in answering questions which subsequently leads to an enhanced teaching and learning of the English language. Equally important, teachers' use of code-switching in the target language instruction can assist the students in understanding the materials due to their lack of target language proficiency.…”
Section: Pedagogical Implicationsmentioning
confidence: 90%
“…For effective and efficient English language teaching and learning, for instance, [29] advises teachers to use code-switching not only as a means to point out main learning themes and other key tasks but also to point out students' errors and to give immediate correction. This practice does not only enhance students' learning of the English language, as [30] discover, but it also does improve students' engagement in answering questions which subsequently leads to an enhanced teaching and learning of the English language. Equally important, teachers' use of code-switching in the target language instruction can assist the students in understanding the materials due to their lack of target language proficiency.…”
Section: Pedagogical Implicationsmentioning
confidence: 90%
“…The review of the literature revealed that many studies tackled the issue of classroom CS from various aspects (Arpac, 2016;Macaro & Tian, 2015;Simasiku, Kasanda, & Smit, 2015;Thompson & Harrison, 2014;Tian & Macaro, 2012). The most common aspects are as follows: the functions and practicality of teacher's CS, the reasons for classroom CS, and the classroom participants' attitudes to CS.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Code-switching is a tool to aid teachers and students both, once the IRJMIS ISSN: 2395-7492  Shafi, S., Kazmi, S. H., & Asif, R. (2020 229 instructors are certain about the right usage and implementation of code-switching strategy in classrooms; that can be taken as linguistically proficient and fulfill their purpose what it is intended for, i.e. "enhancing teaching, learning and concept clarification" (Simasiku et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Aguirre (1988); Sadunih et al, (2018); Hudelson (1983); and Olmedo-Williams (1983), established Code-Switching as an operative teaching and communicative technique which is used preferably among bilingual learners. Ahmad & Jusoff (2009), deduction exposed that beginners appreciate positively the usage of code-switching by teachers in English Language Teaching (as cited in Simasiku et al, 2015). Gulzar (2010), in his study about code-switching in bilingual classrooms of Pakistan, observes that code-switching in language classrooms is done to facilitate the students and students consider that teachers' code-switching actually helps them grasp the difficult ideas.…”
Section: Introductionmentioning
confidence: 99%